2020
DOI: 10.1126/sciadv.aax7945
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible TrxR1 inhibitors block STAT3 activity and induce cancer cell death

Abstract: Because of its key role in cancer development and progression, STAT3 has become an attractive target for developing new cancer therapeutics. While several STAT3 inhibitors have progressed to advanced stages of development, their underlying biology and mechanisms of action are often more complex than would be expected from specific binding to STAT3. Here, we have identified and optimized a series of compounds that block STAT3-dependent luciferase expression with nanomolar potency. Unexpectedly, our lead compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…Redox regulation of STAT3 also occurs via oxidation and reduction of exposed Cys residues, through a redox relay involving peroxiredoxin-2 (Prx2) and thioredoxin-1 (Trx1) [ 83 , 84 ]. Following induction of oxidative stress by H 2 O 2 , Prx2 rapidly oxidizes STAT3 inducing the formation of unphosphorylated STAT3 dimer transcriptionally inactive.…”
Section: Redox Regulation Of Stat1 and Stat3 Signaling Cascadementioning
confidence: 99%
“…Redox regulation of STAT3 also occurs via oxidation and reduction of exposed Cys residues, through a redox relay involving peroxiredoxin-2 (Prx2) and thioredoxin-1 (Trx1) [ 83 , 84 ]. Following induction of oxidative stress by H 2 O 2 , Prx2 rapidly oxidizes STAT3 inducing the formation of unphosphorylated STAT3 dimer transcriptionally inactive.…”
Section: Redox Regulation Of Stat1 and Stat3 Signaling Cascadementioning
confidence: 99%
“…It has become clear that the biochemical and cellular effects of these inhibitors might also be caused by other mechanisms than direct binding to STAT3 in cells [ 15 ]. Recently, we found that several novel STAT3 inhibitors exerted their effects via covalent inhibition of Thioredoxin Reductase 1 (TrxR1, TXNRD1), rather than STAT3.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that several novel STAT3 inhibitors exerted their effects via covalent inhibition of Thioredoxin Reductase 1 (TrxR1, TXNRD1), rather than STAT3. In a cellular setting, inhibition of TrxR1 readily leads to oxidation of STAT3 cysteine residues, thereby impairing the transcriptional function of STAT3 [ 15 , 16 ]. Oxidation of STAT3 cysteine residues leads to the formation of inactive STAT3 multimeric or dimeric covalently bound disulfide-linked complexes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of tyrosine 705 residue induced by epidermal growth factor (EGF) or interleukins can activate STAT-3 in cells [4]. STAT-3 can facilitate cancer progression and metastasis by being constitutively active via various signaling as previously described [5,6]. Abundant evidences have indicated that STAT-3 may be a promising molecular target for cancer treatment.…”
Section: Backgroudmentioning
confidence: 94%